A Ride on The Current State of Silver Nanoparticles in Health: What is The Next Stop? - Adrián Gil-Korilis; Jorge Ergui-Arbizu (Pandawa Institute, 2024)
Silver nanoparticles (AgNPs) are known for their broad scientific and technological applications, among which those related to their bioactivity stand out the most. Its antimicrobial, antioxidant, anti-inflammatory, anti-obesity, antifouling, and biosorption properties have been widely studied and analyzed. Furthermore, numerous strategies are being investigated to overcome the main limitation of AgNPs, their cytotoxicity, such as the development of green chemistry synthesis methods using plant extracts or the use of support materials for controlled release of nanoparticles. However, the methodologies currently used in this line of research limit these nanomaterials from eventually being used in the clinic. It is necessary to implement animal models and interdisciplinary collaboration with biomedical research groups to develop therapies based on AgNPs that may be able to have an impact on the health of patients.